Theoretical Foundations of Approaches to Gender Differentiation - Shodieva Zebiniso Nurmamadovna (Global Scientific Publishing, 2022)
In this article, the author theoretically analyzed approaches to gender differentiation. The differences between men and women have been explained on scientific grounds from a theoretical nature.
Keywords: gender; individ; men and women; biological trait